Modeling the end-use performance of alternative fuels in light-duty vehicles. (15th August 2020) - Kroyan, Yuri; Wojcieszyk, Michal; Kaario, Ossi; Larmi, Martti; Zenger, Kai
Abstract: Present study investigates the end-use performance of alternative liquid fuels in the current fleet of unmodified light-duty vehicle (LDV) engines. Two mathematical models have been developed that represent the way that various fuel properties affect fuel consumption in spark-ignition (SI) and compression-ignition (CI) engines. Fuel consumption is represented by the results from the New European Driving Cycles (NEDC) in order to reflect the end-use impact. Data-driven black-box modeling and multilinear regression methods were applied to obtain both models. Additionally, quantitative analysis was performed to ensure the statistical significance of inputs (p-value below 5%). Fuel consumption (output) of various alternative fuels can be estimated with high accuracy (coefficient of determination above 0.96), knowing fuel properties (inputs) such as lower heating value, density, cetane/octane number, and oxygen content. The validation procedures confirmed the quality of predictions for both models with the average error being below 2.3%. The model performance for the examined fuels such as hydrotreated vegetable oil (HVO) and ethanol blends showed significant C O 2 reduction with high accuracy. Moreover, both models could be used to estimate C O 2 tailpipe emissions and are applicable to various liquid SI/CI fuels for LDV engines. Highlights: Developed models represent the impact of fuel properties on engine performance. The effect on fuel consumption is shown from the end-use perspective. SI models show the effect of RON, density, calorific content, and oxygen content. CI model reveals the effect of cetane number, density, and calorific content. Possibility to predict fuel consumption for new fuel blends.